O nowym eksperymentalizmie bez iluzji. Analiza poglądów Hackinga i Franklina - Czarnocka, Małgorzata (Filozofia Nauki, 1994)
The paper presents an approach to achievements of the new experimentalists that is different from common interpretations functioning in philosophy. The approach also stressed that most of the new experimentalists' programme declarations are not realized in practice.